(untitled) (Simbiótica. Revista Eletrônica, 2023)
In our last years, the figure of vices gained more visibility in the Brazilian political scene. This highlight occurs, above all, after the impeachment process against Dilma Rousseff (PT) in 2014 where her vice Michel Temer (MDB) assumed the presidency of the country. We identified that in the last elections there was a significant increase in women’s candidacies as vices on electoral lists, whether at the national, state or municipal level. Based on this scenario, we investigate the position occupied by the vices, observing data obtained by the TSE and outlining a theoretical analysis of this “phenomenon” in female political representation. Among the results, we observed that after the impeachment, it was strategic for the conservative field to recruit women candidates representing their vision of the world, that is, in the ostensible sense of combating what these sectors classify as feminist approaches.